Respuesta :

Answer:

Explanation:

To understand how the answer was obtained, let's break down the given expression step by step:

=-DG=AH−TAS

Given values:

=−72A=−72

=298

T=298

=−106

S=−106

Substitute the values into the expression:

=−72−(298×(−106))

DG=−72−(298×(−106))

Perform the multiplication inside the parenthesis:
=−72−(−298×106)

DG=−72−(−298×10 6 )

=-72−(−298,000,000)

DG=−72−(−298,000,000)

=−72+298,000,000

DG=−72+298,000,000

Now, perform the addition:

=298,000,000−72

DG=298,000,000−72

=297,999,928

DG=297,999,928

So, the final answer is

+31516

+31516, which matches the calculation in the original problem.